Data Dependence Results for Multistep and CR Iterative Schemes in the Class of Contractive-Like Operators - Karakaya, Vatan; Gursoy, Faik; Dogan, Kadri; Erturk, Muzeyyen (HINDAWI PUBLISHING CORPORATION, 2013)
We intend to establish some results on the data dependence of fixed points of certain contractive-like operators for the multistep and CR iterative processes in a Banach space setting. One of our results generalizes the corresponding results of Soltuz and Grosan (2008) and Chugh and Kumar (2011).
Keywords: FIXED-POINT THEOREMS; APPROXIMATION; MAPPINGS; Mathematics